Maharah Qira’ah pada Buku Teks Bahasa Arab MA Kelas X : Perspektif Teori Mackey - Zidan Nugraha Febriansyah; Hikmah Maulani (JURNALISTRENDI : JURNAL LINGUISTIK, SASTRA, DAN PENDIDIKAN, 2026)
This study analyses the construction of the presentation of maharah qira’ah in the Grade 10 Madrasah Aliyah Arabic textbook based on Mackey’s theory. The study employed a qualitative approach using a (content analysis) design. The data consisted of the maharah qira’ah material in Chapter 1 of the textbook, which was analysed through the four main aspects of Mackey’s theory, namely selection, gradation, presentation, and repetition. The research findings indicate that the qira’ah material in the textbook has systematically applied all four aspects of Mackey’s theory. In terms of selection, the material contains vocabulary and language structures relevant to the themes of self-identity and the madrasah environment. In terms of gradation, the text is structured from general information towards more detailed information, thereby facilitating students’ understanding. In terms of presentation, the meaning of the vocabulary and the content of the reading are supported by the use of images that aid the process of interpretation. In terms of repetition, the exercises presented not only reiterate the information but also encourage pupils to identify, categorise and reconstruct the content of the reading material based on the information obtained from the text. This study demonstrates that the integration of selection, gradation, presentation, and repetition forms a structured reading instruction design that supports the gradual development of meaning comprehension. The contribution of this study is to provide empirical evidence regarding the relevance of Mackey’s theory in the analysis of Arabic teaching materials, particularly in relation to reading skills. These findings also offer a model for evaluating teaching materials based on Mackey’s theory, which can be utilised in the development of textbooks and applied linguistic research in the field of Arabic language learning in madrasahs.